In vitro antioxidant and anti-inflammatory activity of an oleuropein-enriched extract obtained from olives leaves on BME-UV1 cells. Issue 10 (19th May 2023) - Basiricò, Loredana; Mastrogiovanni, Fabio; Lacetera, Nicola; Santi, Luca; Bernini, Roberta; Bernabucci, Umberto
Abstract: In this in vitro study, for the first time was evaluated the antioxidant and anti-inflammatory effect of an Oleuropein-enriched extract (OleE) on bovine mammary epithelial cell line (BME-UV1). OleE was obtained from olives leaves and characterized by HPLC and NMR analysis. Cell viability test indicated that OleE at concentrations of 7.8 up to 250 μg/mL did not exert cytotoxic effect. At concentration of 31.2 up to 250 μg/mL, a dose dependent reduction of ROS production induced by hydrogen peroxide was observed. In addition, OleE at 62.5, 125 and 250 μg/mL showed a dose-dependent reduction in gene expression of TNF, IL1B, and IL10 after exposure to LPS. The downregulation of ROS production and cytokines expression in BME-UV1 by OleE confirmed the antioxidant and anti-inflammatory properties. In vivo experiments will be necessary for future applications of OleE as natural feed supplement in dairy cattle to reduce incidence of oxidative stress in peripartal period. Graphical Abstract: UF0001 Note: Visual Abstract Replacement Requested.